Ultimate displacement of reinforced concrete columns with light transverse reinforcement - Tran, Cao Thanh Ngoc. (2013)
This article presents the analytical and experimental investigations carried out on reinforced concrete (RC) columns with light transverse reinforcement. A semi-empirical model is developed to estimate the ultimate displacement (displacement at axial failure) of RC columns with light transverse reinforcement subjected to simulated seismic loading. The developed model is calibrated using the collected data of RC columns tested to the point of axial failure. A series of experiments is conducted on five RC columns with light transverse reinforcement to validate the applicability and accuracy of the developed model. It is concluded from the study that the mean ratios of the experimental to predicted ultimate displacement and its coefficient of variation are 1.077 and 0.194, respectively, showing a good correlation between the developed model and the experimental data.